Respuesta :
Answer:
[tex]m =-\frac{1}{2}[/tex]
Step-by-step explanation:
The equation of a line in the pending intersection form is:
[tex]y = mx + b[/tex]
Where m is the slope of the line and b is the intersection with the y axis.
In this case we have the following equation
[tex]y-3=-\frac{1}{2}(x-2)[/tex]
To find the slope of this line you must rewrite it in the form
[tex]y = mx + b[/tex]
Then we solve the equation for y.
[tex]y-3=-\frac{1}{2}(x-2)[/tex]
[tex]y=-\frac{1}{2}(x-2)+3[/tex]
[tex]y=-\frac{1}{2}x-2*(-\frac{1}{2})+3[/tex]
[tex]y=-\frac{1}{2}x+1+3[/tex]
[tex]y=-\frac{1}{2}x+4[/tex]
Note that [tex]m =-\frac{1}{2}[/tex]
Finally the slope is: [tex]m =-\frac{1}{2}[/tex]
The slope of the line with equation; y-3 = -1/2(x-2) is; slope, m = -1/2.
According to the question, the equation of the line in discuss is; y-3 = -1/2(x-2).
To determine the slope of the line, we need to rearrange the equation such that it resembles the slope-intercept form of the equation of a straight line as follows;
The equation of a straight line; y = mx + c.
Now, we expand the equation of the line and rearrange as follows;
- y-3 = (-1/2)x -1
- y = (-1/2)x -1 + 3
- y = (-1/2)x + 2.
By comparison, the slope of the line given bey the equation, y-3=-1/2(x-2) is; slope, m = -1/2.
Read more:
https://brainly.com/question/19088520